2006
DOI: 10.1002/ajhb.20588
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dietary intake and helminth infection on diversity in growth among schoolchildren in rural south China: A four‐year longitudinal study

Abstract: The authors carried out six transverse anthropometric, dietary, and parasitological surveys of 274 schoolchildren (138 boys and 136 girls), aged 10-12 years (in 2001), from the Dongting Lake region in rural South China from 2001 to 2005 to examine intra-population differences in growth. Compared to the Chinese references, the subject children were judged to be retarded in growth at the population level. Comparisons among tertiles classified by the extents of change in weight-for-age Z score from the first to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Throughout their childhood growth period, Karimojong boys and girls in this sample became progressively smaller (shorter and lighter) and thinner relative to the NCHS references. They were small as well by comparison with children in other countries in the global south (Adair, 2007;Eveleth and Tanner, 1990;Garnier et al, 2005;Zhou et al, 2007), including nomadic Turkana children (Campbell et al, 2005b;Gray et al, 2004). Their changes in fat stores assumed a similar pattern to that documented for South African children by Cameron et al (1992), but Karimojong children were thinner.…”
Section: Environmental Determinants Of the Growth Of Karimojong Childrenmentioning
confidence: 62%
“…Throughout their childhood growth period, Karimojong boys and girls in this sample became progressively smaller (shorter and lighter) and thinner relative to the NCHS references. They were small as well by comparison with children in other countries in the global south (Adair, 2007;Eveleth and Tanner, 1990;Garnier et al, 2005;Zhou et al, 2007), including nomadic Turkana children (Campbell et al, 2005b;Gray et al, 2004). Their changes in fat stores assumed a similar pattern to that documented for South African children by Cameron et al (1992), but Karimojong children were thinner.…”
Section: Environmental Determinants Of the Growth Of Karimojong Childrenmentioning
confidence: 62%
“…We identified a higher weight gain in girls compared to boys, and in moderate- to heavy-intensity S. mansoni -infected individuals. Several other studies showed benefits on growth catch-up after deworming in chronic schistosomiasis [56, 57]. Yet, interpretation of effects on growth can be complex considering that there are two types of catch-up growth.…”
Section: Discussionmentioning
confidence: 99%
“…Though both stunting and wasting were prevalent in our study, we did not find the associations with schistosomiasis that other investigators have shown. [50][51][52] Our inability to reproduce the association is likely caused by residual confounding from unmeasured variables. The overwhelming support from other studies argues that anthropometry should remain in the toolkit for morbidity assessments.…”
Section: Discussionmentioning
confidence: 99%